3 + 4 = 7 7 x 2 = 14
=7(x+s)
6*(x + 7)
To calculate 4 times the sum of a number and 6, you would first find the sum of the number and 6, then multiply that sum by 4. Let's represent the number as 'x'. So, the sum of the number and 6 would be x + 6. Multiplying this sum by 4 gives you the expression 4(x + 6), which simplifies to 4x + 24.
5(x^2 + y)
what is 4 times the sum of a number squared and 3
28 + 35 = (4 x 7) + (5 x 7) = 9 x 7 = 63
6 divided by the sum of 4 times x and 5 times k is equal to 6 times the reciprocal of (4x + 5k).
(4 x 8) + (7 x 8 ) = 11 x 8 = 88
x-7
5 x 7 and 6 x 7
12 x 7 x 4 = 336